Violence Inflicted on Students with Disabilities in Special Education Institutions at Public Sector: A Remedial Inquiry - Ghulam Fatima (Journal of Business and Social Review in Emerging Economies, 2020)
The central theme of this investigation was to explore types of violence being inflicted on students with disabilities (deaf, blind, mentally retarded and physically handicapped) enrolled at primary grade level in private and public sector Special Education Institutions in Punjab-Pakistan. A sample of randomly selected 5 districts (Lahore, Gujranwala, Okara, Pakpatan, Rawalpindi) out of 36 districts of Punjab was taken. A conveniently available sample of 68 special education teachers (male: 22, female: 46) including 20 Senior Special Education Teachers (SSET) and 48 Junior Special Education Teachers (JSET) was taken to collect data on a self-developed and validated questionnaire with statistically significant reliability index (Cronbach Alpha: 0.85) containing 30 statements on violence on five point Likert type scale (from strongly disagree to strongly agree). The data were collected personally and with the help of research assistants. Data were analyzed on SPSS version 21. Descriptive analysis was run to find frequency distribution of responses, percentages and mean score. Independent sample t-test was employed to find difference in responses of special education teachers on the basis of gender. Analysis of Variance (ANOVA) was run to find difference in the opinions of special education teachers on the basis of their age, qualifications, and teaching experience. There was statistically substantial variation in the responses of special education teachers based on their qualifications. There was not statistically significant difference among the responses of special education teachers on the basis of their gender, age and teaching experience. Conclusions were drawn and recommendations to Punjab Special Education Department were made.